Analisis Hukum Islam Terhadap Pinjaman Uang Elektronik Shopee Paylater Pada Marketplace Shopee - Ananda, Amtricia; Yasin, Ach (Universitas Negeri Surabaya, 2022)
One form of technological development is the existence of Shopee Paylater which provides convenience in shopping with a buy now pay later system. However, people are still unsure about using it, whether the transaction is allowed in Islam or not. This study aims to identify and analyze the practice of using Shopee Paylater as well as a review of Islamic law on Shopee Paylater electronic money loans on the Shopee marketplace. The method used is descriptive qualitative research where the author describes the practice of using Shopee Paylater electronic money which is then studied from the point of view of Islamic law. The results of this study explain that the practice of using Shopee Paylater is not in accordance with sharia principles so it is not allowed because there are several provisions that contain usury with additional payments and fines due, and there are several elements that contradict the DSN-MUI Fatwa No: 116/DSN- MUI/IX/2017 include the use of electronic money obtained by not making a deposit first but in the form of a loan given in the form of a limit, while the limit obtained cannot be disbursed in physical form, and there is usury in it. The use of additional fees or usury can be avoided by using an ijarah contract as a form of application rental fees.